Data in Action : Natural Resources Disclosure for People and Progress - International Finance Corporation (International Finance Corporation, Washington, DC, 2020)
This discussion paper is a product of the From Disclosure to Development (D2D) program, led by the sustainable infrastructure advisory team of the International Finance Corporation (IFC). The program, launched in 2017, is funded by the BHP Foundation and implemented in collaboration with the World Bank. The program’s goal is to enhance benefit sharing with communities from investment in natural resources through effective disclosure and data-use practices. D2D develops and tests new approaches, partnerships, and platforms aimed at improving the ways in which companies and governments disclose data, so that communities and other stakeholders can use it to inform their decisions and actions. To bridge the information asymmetry in the sector and give voice to communities, D2D works to improve the disclosure and use of open data with capacity building, multi-stakeholder dialogues, and data-driven innovation activities with youth, infomediaries, and digital entrepreneurs. The D2D program uses lessons learned from these in-country activities to contribute to global efforts to improve transparency in the natural resources sector through more effective disclosure and use of data. In the coming years, D2D plans to expand to other countries and infrastructure sectors and to add a gender data component.